Maternal pre- and postnatal depression and anxiety: Impacts on childhood asthma and its phenotypes - Kanerva, Eetu; Lukkarinen, Minna; Leppänen, Marika; Pape, Bernd; Rautava, Päivi; Karukivi, Max (Elsevier BV, 2026)
Background
Maternal psychological distress during pregnancy is known to elevate the risk of offspring asthma, but the impact of the timing of the distress remains poorly understood.
Objectives
To assess the individual and combined effects of maternal prenatal and postnatal depressive and anxiety disorders, both separately and longitudinally, on offspring asthma and its phenotypes.
Methods
Healthcare register data on 310,701 children born 2001–2006 and their 232,240 mothers were collected. Maternal depressive disorder was defined by diagnoses F30, F31, F32–F34 and F38 and anxiety disorder as F40–F42, F44–F45 and F48. Timing of disorder was defined as prenatal (from one year before until labor) and postnatal periods (from birth until three years postpartum). Child outcomes were overall asthma diagnosis J45–J46 at 7–12 years, further separated into allergic J45.0 and non-allergic J45.1 asthma phenotypes.
Results
Altogether, 19,000 (6.1%) children had asthma, 6517 (2.8%) mothers had depression, and 4189 (1.8%) had anxiety disorder. Child overall asthma was associated with maternal prenatal depression (adjusted odds ratio 1.28; 95% confidence interval 1.08–1.53) and anxiety disorders (1.30; 1.07–1.57), and with postnatal anxiety disorders (1.33; 1.15–1.54). Both maternal postnatal depression (1.36; 1.06–1.74) and anxiety disorders (1.45; 1.06–2.00) were associated with non-atopic asthma, and postnatal anxiety was associated with atopic asthma (1.34; 1.07–1.67). The comorbidity or longitudinality of maternal depressive and anxiety disorders didn't affect the associations.
Conclusion
Maternal depressive and anxiety disorders were associated with offspring asthma, varying by phenotype and timing. The postnatal effect was significant, suggesting independent associations and possibly distinct pathways in child respiratory morbidity.